Primary hydatid cyst of the mesentery presenting as a small bowel volvulus - Urval, Medha; Pai, B. Srinivas; Mulla, Sameer Ahmed (International Surgery Journal, 2020)
Hydatid disease mostly caused by Echinococcus granulosus (dog tape worm) is a common parasitic disease in pastoral areas. It produces cysts in the human body. Human is an accidental intermediate host. Most common sites are liver and lungs. Intraperitoneal hydatid cyst occurs sometimes and it is usually secondary to rupture of primary hepatic hydatid cyst. Primary intraperitoneal hydatid cyst is rare (2%). Primary hydatid cyst in mesentery is very rare. Small bowel volvulus is rare but documented complication of tumours of the mesentery, including cysts. In this article, the authors present a case of primary mesenteric hydatid cyst with acute intestinal obstruction secondary to volvulus.